Application of Green Accounting Based on University Social Responsibility (USR) At Muhammadiyah University of Bengkulu : A Systematic Literature Review - Izzah Sholehah; Resthi Amandaputri; Lise Salma Nurdia; Rina Yuniarti (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study systematic literature review of 17 articles published between 2023 and 2025 to examine the implementation of green accounting grounded in University Social Responsibility (USR) within higher education institutions. The analysis demonstrates that green accounting contributes to enhancing environmental awareness and promoting stakeholder engagement in sustainability initiatives. However, it concurrently reveals substantial challenges related to reporting and auditing processes, primarily due to the absence of uniform standards and limitations in institutional capacity. This research offers critical insights and formulates recommendations aimed at advancing transparency and accountability in universities' sustainability practices. Its originality stems from the synthesis of contemporary research trends and identified obstacles, providing a foundation for the development of standardized, comprehensive green accounting frameworks tailored to the higher education context. Furthermore, the study underscores the necessity of multi-stakeholder collaboration to facilitate the effective and sustainable adoption of green accounting methodologies in future academic endeavors. Furthermore, the study underscores the necessity of multi-stakeholder collaboration to facilitate the effective and sustainable adoption of green accounting methodologies in future academic endeavors.